Autoantibodies against BAFF, APRIL or IL21 - an alternative pathogenesis for antibody-deficiencies? - Pott, Marian-Christopher (BMC Immunol, 2017)
BACKGROUND: The ability of anti-cytokine antibodies to play a disease-causing role in the pathogenesis of immunodeficiencies is widely accepted. The aim of this study was to investigate whether autoantibodies against BAFF (important B cell survival signal), APRIL (important plasma cell survival signal), or Interleukin-21 (important cytokine for immunoglobulin class switch) present an alternative mechanism for the development of the following primary antibody deficiencies (PADs): common variable immune deficiency (CVID) or selective IgA deficiency (sIgAD). RESULTS: Two hundred thirty-two sera from patients with PADs were screened for autoantibodies against cytokines by ELISA. Statistical data analysis yielded a significant difference (p < 0.01) between the healthy donor sera and both PAD cohorts. The analysis was deepened by subdividing the patient collective into groups with distinct B cell phenotypes but no significant differences were found. For selected sera with notable high ELISA-read outs functional analysis ensued. Anti-BAFF and anti-APRIL antibodies were further examined by a B cell survival assay, whilst the functional relevance of putative anti-IL-21 autoantibodies was investigated by means of a STAT3 phosphorylation assay. However, the results of these experiments revealed no discernible functional effect. CONCLUSION: Whilst statistical analysis of ELISA results showed significant differences between patients and healthy controls, in our set of patients functional tests yielded no evidence for an involvement of autoantibodies against BAFF, APRIL, or IL-21 in the pathogenesis of CVID or sIgAD.